The effect of blocking Notch signaling by γ-secretase inhibitor on allergic rhinitis. (July 2017) - Shi, Le; Ma, Yue; Zheng, Chunquan; Zhang, Qingzhao
Abstract: Objective: This study aimed to investigate the effect of blocking Notch signaling by γ-secretase inhibitor (GSI) on allergic rhinitis. Method: GSI, N-[N-(3, 5-difluorophenacetyl-L-alanyl)]-S-phenylglycine t-butylester (DAPT) was administered to ovalbumin-induced AR mice models intranasally. We observed symptoms of sneezing and nose rubbing. To detect the inflammatory state, the serum OVA-specific-IgE, IFN-γ, IL-4, and IL-5 were analyzed by ELISA, and Th cell cytokines in nasal mucosa were analyzed by RT-PCR, including T-bet, IFN-γ, GATA-3, IL-4, and IL-5. In addition, hematoxylin-eosin (HE) and periodic acid-Schiff (PAS) were applied for histopathological examination. As for the evaluation of Notch signaling, we analyzed the Notch-1, Notch signaling target Hes-1, and Hes-5 in mucosa by RT-PCR, besides, used western blotting and immunohistochemistry to assess NICD (Notch intracellular domain). Results: The results showed that the DAPT ameliorated the development of AR and suppressed Th2 cytokine levels significantly, alleviating eosinophils infiltration and goblet cells metaplasia, suggesting that the GSI can regulate Th2 response and weaken airway inflammation in AR. Conclusion: Our findings provide evidence that blocking Notch signaling by GSI offers high value in treating AR.